Injury, training, biomechanical, and physiological profiles of professional breakdancers - Arundale, A. J.; McNulty, R.; Snyder, C.; O`Brien, J.; Stöggl, T. (International Journal of Sports Physical Therapy, 2023)
Background Breakdancing or breaking will enter the Olympics in 2024, however, there is a paucity of literature exploring the epidemiology, demands, and performance.